The Resistance from a “Third Space”: A Comparative Study of Pakistani and Indonesian Muslims beyond the Dominant Sexual and Gender Norms - Hamzić, Vanja (2011)
This brief study seeks to understand how gender-variant and sexually diverse Muslims in Pakistan and Indonesia encounter and resist two hegemonic identitarian ideological discourses: that of heteronormative Muslim theopolitical reductionism and that of (neo)liberal homonormative identity politics. Through a comparative analysis of the main catalysts of these hegemonic currents and their multifaceted impact on the societal gender/sexual dynamics, several points are made. Firstly, both of these discourses attempt to forcefully produce particular forms of sexuality and gender and to reduce all other expressions and identitary tropes along the sexual/gender continuum. Secondly, in Pakistan as well as in Indonesia, the counter-hegemonic narratives amongst the non-heteronormative and non-homonormative Muslim subjectivities tend to disrupt and transform the two oppressive discourses through a peculiar form of resistance. It is argued that the survival of the researched subjectivities is primarily made possible through emanation of a distinct ‘third space’ these collectives have learned to occupy, which allows them to symultaneously engage with the hegemonic streams and to retain a conceptual and, indeed, spatial distance. Hence, in the final part of this study, some observations are offered of this space and its theoretical and strategic implications.